The Effectiveness of the Google Classroom Application as a Learning Media to Improve Learning Outcomes in Economics Lessons in Classes XI IPS 1 and XI IPS 2 SMAN 1 Bungaraya Siak Regency - Sri Lestari; Gani Haryana; Mujiono Mujiono (Journal of Education Technology Information Social Sciences and Health, 2024)
This research aims to see the effectiveness of the Google Classroom application as a learning medium to improve student learning outcomes. The method used in this research is quantitative descriptive methods. The quantitative descriptive method aims to describe a phenomenon, event, symptom and occurrence that occurs factually, systematically and accurately. The focus of the discussion in this research is to explain and describe the objects of the variables studied. The sample in this study was 29 students of class XI IPS 1 and 29 students of XI IPS 2. Data collection techniques used questionnaires and documentation. Data analysis uses descriptive analysis with analytical tests, Validity Test, Reliability Test, Descriptive Analysis, Normality Test, and Wilcoxon Test. The results of this research show that the use of the Google Classroom application has a positive influence in improving student learning outcomes. The Wilcoxon test results in both classes show an Asymp sig value. (2-tailed) with a value of 0.000 0.05, which means that Google Classroom has a role in improving student learning outcomes.